Improve Insight Self-Meaning Life in Revolution for Success Academic - Sundah, Ariantje; Raya, Mint Husen (Guidance and Counseling Study Program, Pattimura University, 2021)
ABSTRAKTujuan Penelitian ini untuk mengetahui bagaimana keefektifan konseling Adlerian meningkatkan self-meaning untuk success academic. Konseling Adlerian dilaksanakan untuk meningkatkan pemahaman self-meaning dengan desain penelitian pre-tes pos-tes control group. Subjek penelitian yang memperoleh intervensi adalah siswa SMPN 1 Airmadidi dan SMPN 2 Airmadidi, Kabupaten Minahasa Utara Propinsi Sulawesi Utara, tahun ajaran 2020/2021, yang low pemahaman self meaning life. Data angka dianalisis menggunakan uji Two Independent-Sample Test Mann Whitney-U. Hasil eksperimen menunjukkan bahwa melalui konseling Adlerian, pemahaman self-meaning subjek eksperimen dapat meningkat secara berarti. Hal tersebut menunjukkan bahwa higt insiht self-meaning life student merupakan hal esensial fundamental yang membuka kesadaran diri, memicu creative in life style berkompetensi untuk hidup bermakna serta successfull yang memungkinkan self-actualisation di era revolusion industri sebagai peserta didik saat ini, bahkan ke depan dalam menghadapi dunia kerja. Sebagai rekomendasi: (1) konselor harus terampil melaksanakan Konseling yang membantu konseli memahami self-meanning life agar memiliki identitas successfull. (2) perlu dilaksanakan penelitian pelatihan konseling untuk guru Bimbingan Konseling di sekolah. Kata Kunci: konseling Adlerian, makna hidup, makna diri, kesuksesan hidup ABSTRACTThe purpose of this study was to determine how the effectiveness of Adlerian counseling in increasing self-meaning for academic success. Adlerian counseling was carried out to improve understanding of self-meaning with a pre-test post-test control group research design. The research subjects who received the intervention were students of SMPN 1 Airmadidi and SMPN 2 Airmadidi, North Minahasa Regency, North Sulawesi Province, in the 2020/2021 academic year, who had low understanding of self-meaning life. Numerical data were analyzed using the Two Independent-Sample Test Mann Whitney-U. The experimental results show that through Adlerian counseling, the experimental subject's understanding of self-meaning can be significantly increased. This shows that high-insight self-meaning student life is a fundamentally essential thing that opens self-awareness, triggers a competent creative in life style to live a meaningful and successful life that allows self-actualization in the industrial revolution era as students today, even in the future. face the world of work. As recommendations: (1) counselors must be skilled in implementing counseling that helps counselees understand self-meanning life in order to have a successful identity. (2) it is necessary to conduct research on counseling training for Counseling Guidance teachers in schools Keywords: adlerian counseling, meaning in life, self-meaning, life success full